HUBUNGAN KEMATANGAN EMOSI DENGAN KECENDERUNGAN PERILAKU AGRESIF SISWA di SMAN 1 AMPEK ANGKEK - Putri Welly; Fadhilla Yusri; Afrinaldi Afrinaldi; Junaidi Junaidi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study investigates the phenomenon of aggressive behavior among students at SMAN 1 Ampek Angkek, characterized by quarrels, teasing, vandalism, difficulty in managing emotions, and disruptive joking in class. Aggressive behavior in adolescents generally consists of four aspects: Physical Aggression, which includes actions such as hitting, kicking, and other physical attacks; Verbal Aggression, which manifests in insults, sarcasm, slander, and offensive remarks; Anger, referring to feelings of irritation, frustration, and difficulty in controlling emotions; and Hostility, characterized by negative feelings such as jealousy, envy, suspicion, and distrust toward others. The aim of this study was to explore the relationship between emotional maturity and the tendency toward aggressive behavior in these students. Using a quantitative correlational research design, this study surveyed a sample of 86 grade X students, randomly selected from a population of 374 students. Data analysis included normality, linearity, homogeneity, and hypothesis testing using the Pearson Product-Moment correlation formula in SPSS v.20. Findings revealed a correlation coefficient of -0.423, indicating a moderate negative relationship. A significance value of 0.000 (<0.05) confirmed a statistically significant relationship between emotional maturity and aggressive behavior tendencies among students at SMAN 1 Ampek Angkek. These findings suggest that students with higher emotional maturity tend to exhibit lower levels of aggressive behavior.This study investigates the phenomenon of aggressive behavior among students at SMAN 1 Ampek Angkek, characterized by quarrels, teasing, vandalism, difficulty in managing emotions, and disruptive joking in class. Aggressive behavior in adolescents generally consists of four aspects: Physical Aggression, which includes actions such as hitting, kicking, and other physical attacks; Verbal Aggression, which manifests in insults, sarcasm, slander, and offensive remarks; Anger, referring to feelings of irritation, frustration, and difficulty in controlling emotions; and Hostility, characterized by negative feelings such as jealousy, envy, suspicion, and distrust toward others. The aim of this study was to explore the relationship between emotional maturity and the tendency toward aggressive behavior in these students. Using a quantitative correlational research design, this study surveyed a sample of 86 grade X students, randomly selected from a population of 374 students. Data analysis included normality, linearity, homogeneity, and hypothesis testing using the Pearson Product-Moment correlation formula in SPSS v.20. Findings revealed a correlation coefficient of -0.423, indicating a moderate negative relationship. A significance value of 0.000 (<0.05) confirmed a statistically significant relationship between emotional maturity and aggressive behavior tendencies among students at SMAN 1 Ampek Angkek. These findings suggest that students with higher emotional maturity tend to exhibit lower levels of aggressive behavior.